Bakiak and Interpersonal Intelligence on Physical Motor of Children in Khairani Kindergarten of Aceh Besar - Riza Oktariana; Anita Yus; Sanusi Hasibuan (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2019)
Physical motor development is one of the five aspects of early childhood development, to achieve the motoric development, especially rough motoric is done through games. Play activities can stimulate a children’s physical motor development , and become one of the other important factors in improving a children’s psychic interpersonal intelligence. Based on this background, the researchers chose the title “Bakiak and Interpersonal Intelligence on Physical Motor of Children in Khairani Kindergarten of Aceh Besar”. Problems formulation in this study are: Is there any effect of bakiak game on children’s physical motor development , is there any effect of interpersonal intelligence on a children's physical motor development, and is there any interaction of bakiak game and interpersonal intelligence on a children’s physical motor development. The research objectives are: To determine the effect of bakiak game on children's physical motor, to determine the effect of interpersonal intelligence on children's physical motor development and to determine the interaction of bakiak game and interpersonal intelligence on children’s physical motor development . The location of the study was conducted at Khairani Kindergarten in Aceh Besar located in Lubok Batee village, Ingin Jaya Subdistricr, Aceh Besar District. This study was conducted on 15 October to 15 December 2018. The research subject of children's group B which amounted to 30 people, consisting of B1 (15 people) and B2 (15 people). This study was conducted by using experimental methods and research design with treatment by level 2 x 2. The research instrument used were bakiak game, interpersonal intelligence observation sheets and motor physical development tests. Research procedures are pretest, treatment, posttest, data processing, data analysis and conclusion. Meet the instrument validity and reliability standards. Data analysis techniques use descriptive data released by Mean, Median, Mode, frequency distribution table and histogram. Testing the analysis prerequisites that is normality and homogeneity data. From the results of data analysis obtained by this study shows the effect of bakiak game and interpersonal intelligence on physical motor of children in Khairani Kindergarten of Aceh Besar